2003
DOI: 10.1002/marc.200300027
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Vinyl Ethers by (α‐diimine)NiII/Methylaluminoxane Catalysts

Abstract: Polymerizations of vinyl ethers are carried out with (α‐diimine)nickel(II) catalysts in the presence of methylaluminoxane. Effects of structural variations of the ligand on the activities of catalysts and polymer microstructure are described. The catalysts prepared by changing the bulkiness of ligand substituents in the ortho aryl position result in no specific trends terms of the yield and molecular weight of polymer. Poly(vinyl ether)s are atactic regardless of the structure of the catalyst used. magnified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These groups can react with the matrix polymers to form a strong linkage between the matrix and clay. [5][6][7][8][9][10][11][12][13][14] Nevertheless, this type of processing involves an in situ chemical reaction and is sometimes difficult to control. The other type of modification uses surfactants that contain molecular units similar to those of the matrix polymer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These groups can react with the matrix polymers to form a strong linkage between the matrix and clay. [5][6][7][8][9][10][11][12][13][14] Nevertheless, this type of processing involves an in situ chemical reaction and is sometimes difficult to control. The other type of modification uses surfactants that contain molecular units similar to those of the matrix polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The first type includes those reactive surfactants, which contain functional groups, such as hydroxyl groups and double bonds. These groups can react with the matrix polymers to form a strong linkage between the matrix and clay 5–14. Nevertheless, this type of processing involves an in situ chemical reaction and is sometimes difficult to control.…”
Section: Introductionmentioning
confidence: 99%
“…[12,16] According to polymerizations of vinyl ethers with Ni IIbased a-diimine catalysts in combination with MAO, we understood that IBVE and NBVE were cationically polymerized with a moderate yield. [14] There were no specific trends in the yield and molecular weight of the polymer according to the type of catalyst prepared by changing the bulkiness of ligand substituents in the ortho aryl position. The poly(n-butyl vinyl ether) (PNBVE) and poly(isobutyl vinyl ether) (PIBVE) produced by the Ni II catalysts were atactic regardless of the type of catalyst used.…”
Section: Resultsmentioning
confidence: 99%
“…[12] These late-transition-metal complexes are known to be functional-group tolerant, because of their reducing oxophilicity of the cationic metal center. [12,13] We reported that nickel(II)-based catalysts were effective for the polymerization of polar monomers such as vinyl ethers [14] and methyl methacrylate. [15] As a continuation of this type of study, we carried out polymerization of vinyl ethers by using iron(II)-and cobalt(II)-based catalyst systems.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the factors which control the stereoregularity in vinyl ether polymerization by using special Ziegler-type catalysts, [39] metallocene catalysts, [8À10, 40] and postmetallocene catalysts [41]. We have already reported that Ni(II) based catalysts were effective for the polymerization of polar monomers such as vinyl ethers [42] and methyl methacrylate [43]. We have investigated the reactivity of a series of bis(imino)pyridyl iron and cobalt complexes, .…”
Section: Polymerization Of Vinyl Ethersmentioning
confidence: 98%